Modified exergoeconomic analysis method based on energy level with reliability consideration: Cost allocations in a biomass trigeneration system. (August 2018) - Wang, Jiangjiang; Li, Meng; Ren, Fukang; Li, Xiaojing; Liu, Boxiang
Abstract: This paper proposes a modified exergoeconomic method based on energy level with reliability considerations to analyze the cost allocations in a biomass trigeneration system. Energy level is introduced to the exeregoeconomic method to agree with the principle of high energy level with high cost. The system reliability and availability using the combination of state-space and the Markov method is incorporated in the exergoeconomic method to analyze the cost changes for three products in the trigeneration system. The cost influences of failure rate, repair rate, biomass cost and annual operation time are examined to reveal the cost variations with reliability considerations. The cost allocation and sensitivity analysis are presented in a case study. The results indicate that the failure and repair rates of the gasification system largely influences the cost of products from the electricity generation system and the cooling system. The specific exergy cost of the three products with reliability consideration increases approximately 16%. The reduced operation uptime due to component's or subsystem's failure is the key parameter to decrease the revenue at the certain investment and increase the risk cost. Highlights: Propose a modified exergoeconomic analysis method based on energy level. Incorporate system reliability into the exergoeconomic analysis. Discuss the cost allocations in a biomass trigeneration system. Present the influences of failure rate, repair rate and operation time to production cost.